Charge transfer in collisions of Beq+ (q=2-4) and Bq+ (q=3-5) ions with H. (15th January 2015) - Wu, Y; Liu, L; Liu, C H; Qu, Y Z; Wang, J G; Janev, R K
Abstract: The charge transfer reactions in collisions of Be q+ (q=2-3) and B q+ (q=3-4) ions and atomic hydrogen are investigated by using the quantal molecular orbital close-coupling (QMOCC) and the two-center atomic-orbital close-coupling (TC-AOCC) methods. Total and sub-shells state-selective cross sections are calculated for low and intermediate energy region and compared with other data available. Sets of recommended cross sections, based on the QMOCC and TC-AOCC calculations, are deduced and tabulated for Be 2, 3+ + H and B 3, 4+ + H collisions, which provide important atomic data needed in the charge-exchange-recombination spectroscopy diagnostics in magnetic fusion plasmas investigation.